Pengaruh Digital Marketing, Kualitas Produk Dan Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada Toko Kue Galies Cake (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2025)
Competition in the food and beverage industry is becoming increasingly intense, marked by the dynamic nature of consumer preferences and continuous product innovation. To achieve success and sustainability, culinary businesses must prioritize customer satisfaction. This study aims to examine the influence of digital marketing, product quality, and service quality on customer satisfaction at Galies Cake Bakery.The research was conducted at Galies Cake Bakery, with a population of 95 consumers. The study used an infinite sample and applied an accidental sampling method, where respondents were selected based on their availability and willingness to participate. Data collection methods included observation, interviews, and questionnaires. The analytical techniques employed were validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, coefficient of determination analysis, t-tests, and F-tests.The hypothesis testing results indicate that (1) digital marketing has a positive and significant effect on customer satisfaction, (2) product quality has a positive and significant effect on customer satisfaction, (3) service quality has a positive and significant effect on customer satisfaction, and (4) simultaneously, digital marketing, product quality, and service quality have a positive and significant effect on customer satisfaction. The R² coefficient of 75.2% demonstrates that digital marketing, product quality, and service quality contribute to customer satisfaction at Galies Cake.It is recommended that Galies Cake enhance customer satisfaction by improving product quality, pricing strategies, services, and digital marketing transparency. For future research, it is suggested to include additional variables such as location, price, and store atmosphere and to conduct studies in different locations for broader insights.